Beta-actin variant is necessary for Enterovirus 71 replication - Lui, Edmund Yan Long; Lin, Zhiyang; Lee, Jia Jun; Chow, Vincent Tak Kwong; Poh, Chit Laa *; Tan, Eng Lee (Elsevier, 2013)
Enterovirus 71 (EV71) is one of the main etiological agents of the Hand, Foot and Mouth Disease (HFMD) and has been known to cause fatal neurological complications such as herpangina, aseptic meningitis, poliomyelitis-like paralysis and encephalitis. EV71 is endemic in the Asia-Pacific region and causes occasional epidemics. In order to better understand EV71 infection, we compared the proteome between EV71-susceptible and EV71-resistant human Rhabdomyosarcom a(RD)cell line. We found significant differences in the b-actin variants between the EV71-susceptible RD cells and EV71-resistant RD cells, suggesting that b-actin, in association with other proteins such as annexin 2 is required in vesicular transport of EV71. This finding further support our previous study that actin potentially plays a role in pathogenesis and the establishment of the disease in HFMD.